TOURISM DEVELOPMENT STRATEGY AS A DRIVE ECONOMIC POTENTIAL OF BALIKPAPAN CITY - Aprioyono, Achmad; Harbani, Parikesit Sukma; Dwiputri, Inayati Nuraini (Nusantara Economics and Entrepreneurships Journals, 2024)
Balikpapan City as the gateway to the IKN region, has the potential to showcase its coastal richness in the development of maritime tourism. This research aims to identify the potential for maritime tourism development in Balikpapan and the strategies for developing maritime tourism in the city. The study employs a mixed-methods approach, specifically an explanatory design. The research focuses on three areas: Susur Teluk Beach, Manggar Segarasari Tourist Beach, and the Graha Indah Mangrove Forest. The variables in this study include attraction elements, accessibility elements, amenity elements, as well as supporting infrastructure and facilities. Data collection techniques involve observation, interviews, and questionnaires. The data analysis technique employed is SWOT analysis. The results indicate that the potential for maritime tourism in Balikpapan can be divided into two categories: event-based and conservation-based. Event-based destinations can be implemented at Manggar Beach, while conservation-based tourism can be applied at the Graha Indah Mangrove Center. The development strategy for maritime tourism in Balikpapan should involve a legal foundation to ensure integrated policies, coordination among stakeholders, community involvement, and the enhancement of the quality of human resources managing maritime tourism